Integration of Knowledge: A Time Befitting Step - Ghalia, Bouhedda; Hossen, Belayet (‘Abqari Journal, 2019)
This research aims to demonstrate that in the contemporary world, secular philosophical thought seized not only the Western education system but also that of Muslim World. The Western materialist thoughts are mostly originated from empiricism, rationalism, secularism and many more tenets as such. Hence, their such speculation distanced them from the guidance of Allah (SWT); eventually, many sorts of rebellious actions prevailed in their perceptions, policies of society and state. Conversely, Islamic epistemology is different. It creates connection between all sources of knowledge and revelation. The purpose of this study is to display the moral failure of secular education system and dire necessary of integrated education and its swift expansion, especially for Muslims across the Islamic world. The study has followed the qualitative methodology through an intensive study mainly the secondary data like the previously published original books, articles, periodicals, magazines and online lectures of specialists and experts on integration of knowledge. The findings of the research are installing Islamic worldview in mindset of Muslim students, producing innovative dynamic leadership for each sector, launching same education system and joint research project for OIC member states, nurturing thinking mind of students, making people employable, expanding exchange program, revitalizing higher education and building relationship between universities and industries.